Development and optimization of mucoadhesive microballons of nizatidine for management of peptic ulcer - Seema Jain; Neha Jain; Mohan Lal Kor; Umesh Kumar Jain; Abhishek Kumar Jain (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2020)
The mucoadhesive microballons prepared by using combination of Poly Acrylic Acid (PAA), Poly Vinyl Pyrrolidone (PVP) polymers by polymer-polymer combination with solvent diffusion method. It is managing the discharge rate of Nizatidine between therapeutic absorption windows by extended the gastric emptying time of formulation. The delivery systems make certain accessibility of drug content at the assimilation site for the preferred period of time. The present work was justified effect of various parameters as polymer (PAA-PVP) concentration, drug concentration, internal phase/external phase ratio, surfactant concentration, stirring speed, stirring time. PAA-PVP polymeric combinations microballons were prepared by solvent dispersion technique. The effect of internal/external phase ratio on preparation of microballons shows that content of water in the internal phase played a key role in the formation of microballons. The particle size found to be decreased upon increasing the concentration of surfactant (span 80) in oil phase. This might be due to the increase the surface tension of aqueous phase which ultimately seem to allow the formation of micro size range. The present work confirmed that any criteria can be effect the result of the shape, size and size distribution, entire medication load of microballons.